Adaptive low density parity check encoder for a complete free space optics/continuous variable-quantum key distribution system using commercially available off-the-shelf devices for variable throughput network considering dynamical atmospheric turbulence levels - López-Leyva, Josué Aarón; Arvizu Mondragón, Arturo; Santos Aguilar, Joel; Ramos García, Raúl; Talamantes-Álvarez, Ariana (My University, 2018)
In this paper, an adaptive low density parity check (LDPC). encoder for complete Free Space Optics/Continuous Variable-Quantum Key Distribution (FSO/CV-QKD) system using a Commercially available Off-The-Shelf (COTS) device for emulated dynamical atmospheric turbulence levels is presented. The experimental and emulation results show the maximum and minimal final secret key rates of ≈ 105 Kbps and ≈ 10 Kbps, respectively, for minimal and maximal throughput in a commercial network, 30 Mbps and 90 Mbps, respectively. Our proposal presents an adequate performance for weak and moderate atmospheric turbulence levels and a suitable option for improving the use of Quantum Key Distribution (QKD) systems.
Revista mexicana de física
Keywords: Adaptive encoder; Atmospheric turbulence; COTS device